Pengaruh Pembelajaran Daring terhadap Kemampuan Guru Mengelola Proses Pembelajaran di MAN 1 Musi Banyuasin - Sumiyati (Yayasan Sembilan Pemuda Indonesia, 2021)
The aim of this study was to see how online learning affected teachers' ability to manage the learning process at MAN 1 Musi Banyuasin. Purposive sampling was used to select 20 teachers from MAN 1 Musi Banyuasin for this study. Data was collected by handing out questionnaires with a 5-point Likert scale measuring 20 statement items. Multiple linear regression analysis was used as the method of analysis. The findings revealed that simultaneous online learning improved teachers' ability to manage the learning process significantly.